Structural Performance of the RC T-Girder Superstructure of Gongabu Bridge under Vehicular Loads - Neupane, Bini (International Journal on Engineering Technology and Infrastructure Development, 2025)
This research focuses on the structural assessment of a reinforced concrete T-girder bridge located near Gongabu Buspark in Kathmandu, which spans the Bishnumati River. The bridge was selected for analysis due to its age, visible signs of deterioration, and its role in supporting daily urban traffic. Linear Static Analysis and Moving Load Analysis was carried out in CSI Bridge version 20.2.0 for serviceability, structural strength and equilibrium load combinations given in IRC 6:2017. The deflections, forces and stresses for linear static and moving load analysis were obtained and checked for the permissible values. The analyses revealed that the deflection during the moving load analysis exceeded the maximum permissible limit, which may be a contributing factor to the longitudinal cracks observed during visual inspection. However, other factors such as aging of concrete, environmental effects, and inadequate maintenance may also have played a significant role in the deterioration.